Chapter 2 Normative economic statecraft China's quest to shape the world in its image - Mattlin, Mikael (Taylor & Francis, 2021)
This chapter provides an overview of state-of-the-art research revolving around China's use of economic and financial means to serve foreign policy objectives with normative implications, defined here as normative economic statecraft. The chapter's overview of China's use of economic statecraft reveals its breadth and diversity. China also indirectly challenges existing international norms of economic governance by its alternative modus operandi. As China does not always proclaim its challenge to existing norms, this paper suggests an analytical distinction between stated and concealed normative objectives. Much of China's challenge to global economic governance norms is concealed. Research on China has revitalized old debates on economic statecraft and geoeconomics, and reoriented their focus from economic coercion (e.g., sanctions) to economic inducements, and alternative institutions and norms. This subfield of China studies thus has a scholarly impact beyond the area studies specialization